2017
DOI: 10.5897/jgmr16.0263
|View full text |Cite
|
Sign up to set email alerts
|

Artisanal gold mining in Batouri area, East Cameroon: Impacts on the mining population and their environment

Abstract: Batouri is located in the East region of Cameroon; geologically the area is made up of Pan African granitoids, which are the host rocks of gold mineralization. Batouri gold deposits have long been subjected to artisanal mining activities carried out by the indigenes for livelihood. Majority of the mining population (45%) is made up by youths (15-30 years), followed by the adults (35%) within the age range 46-60 years old. Adults within the age range 31-45 years constitute only about 5% of the mining population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Miners and stakeholders were identified, approached, and interviewed through snowball sampling and the support of assistants in the mining company in the Rutsiro mining site. Methodology of snowball sampling is used in similar research by Bansah et al [14] in Ghana and also by Kouankap et al [15] in Cameroon, by Arthur-Holmes [16] in Ghana, and by Baffour-Kyei et al [17] in Ghana and Postma and Geenen in Rwanda [18]. Snowball sampling was chosen due to the suitability of the participants in the case study.…”
Section: Study Setting and Designmentioning
confidence: 99%
“…Miners and stakeholders were identified, approached, and interviewed through snowball sampling and the support of assistants in the mining company in the Rutsiro mining site. Methodology of snowball sampling is used in similar research by Bansah et al [14] in Ghana and also by Kouankap et al [15] in Cameroon, by Arthur-Holmes [16] in Ghana, and by Baffour-Kyei et al [17] in Ghana and Postma and Geenen in Rwanda [18]. Snowball sampling was chosen due to the suitability of the participants in the case study.…”
Section: Study Setting and Designmentioning
confidence: 99%
“…Majority of our subjects (88.3%) had attended some schooling, and the highest level of education attained was secondary education. Sana et al, (2017) in Burkina Faso revealed that over two third of the artisan miners in their study were without any formal education, while two previous studies in Cameroon showed that the highest level of education attained by a majority was primary level (Kouankap et al, 2017;Ralph et al, 2018). The very fact that ASGM is a poverty-driven activity could explain its negative impacts on education.…”
Section: Sociodemographic Characteristicsmentioning
confidence: 73%
“…Recruitment of study participants and selection of the mining sites was done through nonprobability convenience sampling based on participants' involvement in ASGM, and proximity of the mining sites respectively. A total of 60 participants were recruited as follows: Batouri (18), Kette (17), Ngoura (12) and Bétaré-Oya (13).…”
Section: Study Population and Samplingmentioning
confidence: 99%
“…Hentschel, Hruschka, and Priester in their joint publications: Global Report on Artisanal & Small-Scale Mining [14] and Artisanal and Small-Scale Mining-Challenges and Opportunities [38] focus on socioeconomic aspects that accompany the environmental aspects of ASM. ASM is often mentioned in connection with gold mining, where environmental degradation occurs as a result of mercury usage [31,[39][40][41][42][43][44][45]. Mercury can then contaminate water resources, soil, air, and can also enter the human body, as confirmed by research in mining sites around the world.…”
Section: Resultsmentioning
confidence: 99%